Carbon utilization and storage through rehabilitation of groundwater wells - Vivek V. Patil; Gabriella Basso; Steven Catania; Christopher Catania; Timothy Ostapuk; Robert Vince (Scientific Reports)
Abstract According to the Intergovernmental Panel on Climate Change (IPCC) of the United Nations (UN), rise in atmospheric concentration of carbon dioxide (CO $${_2}$$ 2 ) due to anthropogenic factors is considered as the primary driver for global climate change. With almost every major corporation around the world working towards their “net-zero goals”, it is becoming increasingly important to have more technologies that can help reduce carbon footprint. Achieving sequestration of CO $${_2}$$ 2 in the subsurface through Carbon Capture Utilization and Storage (CCUS) technologies like CO $${_2}$$ 2 -Enhanced Oil Recovery, CO $${_2}$$ 2 -Enhanced Geothermal Systems, CO $${_2}$$ 2 -Enhanced Coal Bed Methane, etc. is well accepted. We introduce yet another attractive CCUS opportunity through well rehabilitation. Aqua Freed® and Aqua Gard® are well-known well rehabilitation and preventive well maintenance technologies that utilize (inject underground) liquid CO $${_2}$$ 2 for the purpose. The goal of this study was to quantify the storage capacity of Aqua Freed® and Aqua Gard®, and establish their CCUS credentials. Depending on the well being serviced, these technologies can inject up to 40 US tons of CO $${_2}$$ 2 per well. Based on field data collection and statistical modeling, we estimated that 82–96% (median 90%) of the injected CO $${_2}$$ 2 remains in the subsurface post injection. Overall, our results and analysis of the US market suggest that using CO $${_2}$$ 2 for well rehabilitation and maintenance has a storage potential of several megatonnes of CO $${_2}$$ 2 annually in the US alone.